2017
DOI: 10.24251/hicss.2017.518
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Adoption of Wearable Computers in Enterprises - Results of Analyzing Influencing Factors and Challenges in the Industrial Sector

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…When introducing AR technologies, companies encounter different influencing factors, challenges and obstacles. Based on expert interviews, the authors in [8] identified 11 influencing factors and 25 associated challenges in the implementation and use of wearables. The influencing factors were grouped into three super categories: Technological, organizational and environmental (e.g., data protection and security).…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…When introducing AR technologies, companies encounter different influencing factors, challenges and obstacles. Based on expert interviews, the authors in [8] identified 11 influencing factors and 25 associated challenges in the implementation and use of wearables. The influencing factors were grouped into three super categories: Technological, organizational and environmental (e.g., data protection and security).…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…Most of the AR research in the last 20 years has come from the scientific domain [13], with fewer reports on industrial AR applications. Moreover, most of the research deals with technical aspects of assistance systems [8]. There are not many deployment reports and applications in enterprises yet.…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Einblendung von Packlisten in das Sichtfeld von Logistikmitarbeitern verbessert die Prozesseffizienz [29]. [36]. Jedoch untersuchen die Autoren die Adoption von Wearables im Allgemeinen und adressieren nicht die Charakteristika von KMU.…”
Section: Augmented Reality Smart Glasses In Der Intelligenten Fabrikunclassified
“…[18]) konnte der Einfluss von Wettbewerbern auf die Technologieadoption in der vorliegenden Untersuchung nicht bestätigt werden. Vielmehr ist festzustellen, dass Rahmenbedingungen wie fehlende Sicherheitsregularien und Datensicherheitsbedenken die Adoption von ARAS und Wearables im Allgemeinen beeinflussen [36]. Es kommt hinzu, dass die Verfügbarkeit von Entwicklern für Augmented-Reality-Devices die Diffusion der Technologie beeinträchtigt.…”
Section: Diskussion Und Ausblickunclassified